Brief Report: Endothelial Colony-Forming Cells and Inflammatory Monocytes in HIV. (15th April 2015) - Hays, Travis R.; Mund, Julie A.; Liu, Ziyue; Case, Jamie; Ingram, David A.; Gupta, Samir K.
Abstract : Abstract: The relationships between HIV infection, monocyte activation, and endothelial colony-forming cells (ECFCs) are unknown. We compared ECFC, intermediate monocytes (CD14 + CD16 + ), and nonclassical monocytes (CD14 dim CD16 ++ ) levels in HIV-infected participants virologically suppressed on antiretroviral therapy, HIV-infected treatment-naive participants, and HIV-uninfected healthy controls. ECFC levels were significantly higher in the HIV-infected virologically suppressed group compared with the uninfected controls. CD14 + CD16 + percentages (but not CD14 dim CD16 ++ cells) were significantly higher in both HIV-infected groups vs. uninfected controls. In the HIV-infected groups, ECFCs and CD14 + CD16 + intermediate monocytes were significantly and inversely correlated. Lower availability of ECFCs may partly explain the relationship between greater intermediate monocytes and atherosclerosis in HIV. Abstract : Supplemental Digital Content is Available in the Text.